2020
DOI: 10.1002/jctb.6585
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fish scale biosorbent in the treatment of seafood processing plant wastewater

Abstract: BACKGROUND Wastewater generated from seafood processing plants poses a serious threat to the draining environments. In addition, huge amount of fish scales are discarded as solid waste from seafood processing plants and fish markets. These biowastes can be used as biosorbent in the treatment of wastewaters. In the present work, waste fish scales were employed as biosorbent in order to explore the adsorption capacity of several pollutant parameters such as nutrients, ammonia, biological oxygen demand (BOD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This high reduction percentage observed in the present study might be due to the high surface area of biochar (347 m 2 /g) compared with the previous report (1.83 m 2 /g). Another report registered >90% removal of BOD and COD using chemically modified (acid treated) fish scale biosorbent in the treatment of 100 mL wastewater 13 . Thus, it is very clear that, the present work is the first study to involve the generation of novel fish scale biochar with high surface area when compared with other fish scale adsorbents employed in previous works.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…This high reduction percentage observed in the present study might be due to the high surface area of biochar (347 m 2 /g) compared with the previous report (1.83 m 2 /g). Another report registered >90% removal of BOD and COD using chemically modified (acid treated) fish scale biosorbent in the treatment of 100 mL wastewater 13 . Thus, it is very clear that, the present work is the first study to involve the generation of novel fish scale biochar with high surface area when compared with other fish scale adsorbents employed in previous works.…”
Section: Resultsmentioning
confidence: 70%
“…Another report registered >90% removal of BOD and COD using chemically modified (acid treated) fish scale biosorbent in the treatment of 100 mL wastewater. 13 Thus, it is very clear that, the present work is the first study to involve the generation of novel fish scale biochar with high surface area when compared with other fish scale adsorbents employed in previous works. Moreover, the results of this study showed that fish scale biochar can also be effectively utilized as an alternative for commercially available AC since both adsorbents displayed almost similar %R and adsorption potential in the removal of pollutant parameters such as BOD and COD during the effluent treatment process.…”
Section: Effect Of Adsorbent Dosage Level and Treatment Timementioning
confidence: 85%
See 2 more Smart Citations
“…Dried fish scales can be used in wastewater treatment systems as a flocculating agent to precipitate the solid material, particularly protein materials [ 64 ]. Dried fish scales are cheaper than chitosan and safer than traditional flocculating agents [ 52 ].…”
Section: Industrially Producible Fish Productsmentioning
confidence: 99%